Probability, Statistics, and Stochastic Processes for Engineers and Scientists - Haghighi, Aliakbar Montazer, author 517366; Wickramasinghe, Indika 636173 (Boca Raton, FL : CRC Press, 2021)
"Featuring recent advances in probability, statistics, and stochastic processes, this new textbook presents Probability and Statistics, and an introduction to Stochastic Processes. The book presents key information for understanding the essential aspects of basic probability theory and concepts of reliability as an application. The purpose of this book is to provide an option that combines these areas into one resource, balancing both theory, practical applications, and also keeping the practitioners in mind"--